2019
DOI: 10.1590/0001-3765201920180097
|View full text |Cite
|
Sign up to set email alerts
|

Mercury exposure of children living in Amazonian villages: influence of geographical location where they lived during prenatal and postnatal development

Abstract: Introduction: In some Amazonian river basins, hair mercury concentration is above the recommended levels. We evaluated the influence of birth geographical location in the hair mercury level of Amazonian riverine children. materials and methods: hair mercury concentration was measured in 219 children living in four Amazonian riverine communities: Tapajós River (São luiz do Tapajós and Barreiras villages, n = 110), Tocantins River (limoeiro do Ajurú village, n = 61), and Caeté River (Caratateua village, n = 48).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
9
0
3
Order By: Relevance
“…There is a long and ongoing history of gold mining activities in the Tapajos River basin and its impacts are well documented [5,13,14,41,43,63,64,66,67,[108][109][110]. It is widely known that artisanal gold mining activities are responsible for emitting 200 metric tons of mercury annually; approximately 27% of global emissions are discarded annually without any control [111,112], constituting a potential risk to human health and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…There is a long and ongoing history of gold mining activities in the Tapajos River basin and its impacts are well documented [5,13,14,41,43,63,64,66,67,[108][109][110]. It is widely known that artisanal gold mining activities are responsible for emitting 200 metric tons of mercury annually; approximately 27% of global emissions are discarded annually without any control [111,112], constituting a potential risk to human health and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Given the current federal government's effort to create strategies to facilitate the invasion of protected areas in the Amazon by garimpeiros and mining industries, it is essential to clarify that the contamination of fish by mercury and all related health damages are caused (or intensified) by exploitation of gold. Many studies have already shown mercury contamination in the fauna of the Tapajós River Basin at least two decades ago [55][56][57][58][59][60][61][62][63][64][65]. Dórea et al [59] detected mean mercury levels in piscivorous fish of 0.578 µg/g and 0.052 µg/g Hg in non-piscivorous in the upper Tapajós basin, whilst Brabo et al [56] investigated fish contamination in the Sai Cinza region, also inhabited by indigenous Munduruku.…”
Section: Discussionmentioning
confidence: 99%
“…As an organic form of Hg, MeHg has extremely neurotoxic effects and is readily accumulated in biota due to its lipophilic and protein-binding properties [102,103]. A series of studies have shown the average levels of contamination of aquatic species in the Brazilian Amazon [49,[52][53][54][55][56][57][58][104][105][106][107][108][109]. For example, contamination can reach 0.13 to 2.85 µg Hg/g for certain fish species [104] and Dórea et al [55] detected mean mercury levels of 0.578 g Hg/g piscivorous fish and 0.052 g Hg/g non-piscivorous fish in the upper Tapajós basin.…”
Section: Methylmercury Absorption By Fishmentioning
confidence: 99%
“…A vast body of literature has analyzed the increase in contamination levels in the Amazon population [47][48][49][50][51][52][53][54][55][56][57][58]. Vasconcellos et al [49] found an average methylmercury hair level of 7.0 µg/g in the Munduruku indigenous community in Tapajós and Vega et al [58] observed that the Yanomami indigenous community, also in Brazil, had hair methylmercury levels higher than 6.0 µg/g, which is far above the maximum recommended level of 1.0 µg/g by the United States Environmental Protection Agency (U.S.EPA) [59] and 2.3 µg/g recommended by The Food and Agriculture Organization of the United Nations (FAO/WHO) [60].…”
Section: Introductionmentioning
confidence: 99%